Developing and Validating Trust Measures for e-Commerce: An Integrative Typology - McKnight, D. Harrison; Choudhury, Vivek; Kacmar, Charles (Information systems research, 2002)
Evidence suggests that consumers often hesitate to transact with Web-based vendors because of uncertainty about vendor behavior or the perceived risk of having personal information stolen by hackers. Trust plays a central role in helping consumers overcome perceptions of risk and insecurity. Trust makes consumers comfortable sharing personal information, making purchases, and acting on Web vendor advicebehaviors essential to widespread adoption of e-commerce. Therefore, trust is critical to both researchers and practitioners. Prior research on e-commerce trust has used diverse, incomplete, and inconsistent definitions of trust, making it difficult to compare results across studies. This paper contributes by proposing and validating measures for a multidisciplinary, multidimensional model of trust in e-commerce. The model includes four high-level constructsdisposition to trust, institution-based trust, trusting beliefs, and trusting intentionswhich are further delineated into 16 measurable, literature-grounded subconstructs. The psychometric properties of the measures are demonstrated through use of a hypothetical, legal advice Web site. The results show that trust is indeed a multidimensional concept. Proposed relationships among the trust constructs are tested (for internal nomological validity), as are relationships between the trust constructs and three other e-commerce constructs (for external nomological validity), as Web experience, personal innovativeness, and Web site quality. Suggestions for future research as well as implications for practice are discussed.